MAKNA LEKSIKAL PERMAINAN RAKYAT MELAYU SAMBAS: PENDEKATAN ETNOLINGUISTIK - Agus Syahrani; Amriani Amir; Sabhan Rasyid (Jurnal Elektronik WACANA ETNIK, 2011)
This study focuses on the observation of cultural object, that is folk games. The referred folk games are traditional games played by the local people. Acquisition of data conducted in the 19 subistrict of Sambas, West Kalimantan. Researcher uses qualitative research method, specifically by translating the vocabulary data of Malay folk games in the District of Sambas. This study also uses ethnolinguistic approach that views the relationship between language and cultural elements within Malay community in Sambas. Analysis conducted by researcher towards the collected data is the type of meaning analysis based on the classification of tools, techniques, player name, and the name of the folk game.By virtue of research, researcher accumulated 173 words as research data. All of data comprise of 30 kind of folk games with classification, that is 51 words as tools, 44 words as techniques, 4 words as player name, and 30 words as the name of the folk games classification.